Ghana Private Equity and Venture Capital Ecosystem Study - Divakaran, Shanthi (World Bank, Washington, DC, 2018)
This paper discusses the landscape for private equity and venture capital financing in Ghana. It provides an overview of the private equity and venture capital market in the country, describing key players, including funds, fund managers, investors, and public sector entities. The paper provides an analysis of key market drivers and impediments, as well as legal, regulatory, and taxation drivers and impediments that affect Ghana’s private equity and venture capital industry.